Efforts to Develop Emotional Intelligence Through Social Personal Guidance for Students of SMP Islam Ulul Albab Lubuklinggau City - Ahmadi; Dina Hajja Ristianti (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This research was conducted to find out in depth the profile of emotional intelligence of students of Islamic Ulul Albab Lubuklinggau Junior High School and how efforts to implement personal-social guidance are appropriate for the development of emotional intelligence of students of Islamic Ulul Albab Lubuklinggau Junior High School. The method used in this research is qualitative descriptive model and the data obtained through a series of observation processes, interviews, documentation and the peak is analyzed by triagulation techniques. This research obtained the following conclusions: 1) The intelligence profile of students of Islamic Ulul Albab Lubuklinggau Junior High School is low, this is as stated by the teacher of guidance and counseling and also the principal of Islamic Ulul Albab Lubuklinggau Junior High School and supported by the statements of several students of Islamic Ulul Albab Lubuklinggau Junior High School; 2) Social personal guidance provided at Islamic Ulul Albab Junior High School is focused on providing direction to students regarding personality or akhlakul karimah and social problems that are focused on how students interact with the people around them. The method used by counseling guidance teachers is by means of group methods or by providing guidance in a structured and group manner with a predetermined schedule.